Changes in the position of the Subtropical Front south of New Zealand since the last glacial period. (14th July 2015) - Bostock, Helen C.; Hayward, Bruce W.; Neil, Helen L.; Sabaa, Ashwaq T.; Scott, George H.
Abstract This study fills an important gap in our understanding of past changes in the Southern Subtropical Front (S‐STF) in the southwest Pacific Ocean. Paleo‐sea surface temperatures (SST) were estimated from planktic foraminiferal census counts from cores straddling the modern S‐STF in the Solander Trough, south of New Zealand. The estimated SST were compared for 6 time slices; glacial period (25–21 ka), Last Glacial Maximum (LGM; 21–18 ka), early deglaciation (18–16 ka), late deglacial/early Holocene period (14–8 ka), mid‐Holocene period (8–4 ka), and late Holocene period (4–0 ka). The position of the S‐STF was determined by two methods: (1) the location of the 10°C isotherm and (2) the location of the highest SST gradients. These new results suggest that the S‐STF was not continuous between east and west of New Zealand during the glacial period. Steep SST gradients indicate that a strong S‐STF rapidly shifted south during the LGM and early deglaciation. During the late deglacial and Holocene periods the position of the S‐STF differs between the two methods with reduced SST gradients, suggesting a more diffuse S‐STF in the Solander Trough at this time. The glacial SST data suggest that the S‐STF shifted north to the west of New Zealand, while to the east there was a stronger SST gradient across the front. This was possibly the result of an increased wind stress curl, which could have been caused by stronger, or more northerly Southern Hemisphere westerly winds (SHWW), or a merging of the SHWW split jet in this region.